Child development : an active learning approach - Levine, Laura E.; Munsch, Joyce (Canada : SAGE, 2017)
With its hallmark active learning approach, the second edition of this topically organized text is the most interactive introduction to child development today. Dynamic learning activities in each chapter invite students to forge a personal connection to the topics shaping the field, including neuroscience, diversity, culture, play, and media.
Understanding Development: Why and How We Study Children and Adolescents -- Introduction: Issues in Child Development -- Theories of Development -- How we Study Development -- Beginnings: How Children Develop: Nature Through Nurture -- Prenatal Development, Birth, and the Newborn -- Building Blocks of Development: How Children Grow -- Physical Development: The Body and the Brain -- Cognitive Development -- Intelligence and Academic Achievement -- Language Development -- Emotional Development and Attachment -- Identity: The Self, Gender, and Moral Development -- Social Development -- Contexts for Development: Families -- Beyond Family and School: Activities, Media, and the Natural World -- Health, Well Being, and Resilience.
Includes bibliographical references and index.
Keywords: Child psychology; Child development